Efficiency of Tax Administration and Its Influence on Taxpayer Compliance - Mukhammad Idrus (STIE Amkop Makassar, 2024)
The purpose of this study is to examine the multifaceted factors influencing tax administration efficiency and taxpayer compliance, including legal frameworks, cultural norms, economic conditions, and technological advancements. The research design and methodology involve a comprehensive review and synthesis of existing literature on tax administration and compliance, incorporating empirical studies, theoretical frameworks, and comparative analyses. Findings indicate that efficient tax administration, supported by robust legal frameworks, effective human capital investments, and modern technological solutions, significantly contributes to higher taxpayer compliance rates. Additionally, cultural attitudes towards taxation and economic stability play crucial roles in shaping compliance behavior. The implications of these findings underscore the importance of adopting a holistic approach to tax administration, which balances deterrence with trust-building measures and emphasizes continuous investment in capacity building, legal reforms, and technological innovations. This study informs policymakers and tax authorities about strategies to enhance administrative efficiency, promote voluntary compliance, and design responsive tax systems capable of adapting to changing economic and technological landscapes.